Sustainability as a “magic concept” - Trond Ove Tøllefsen (Cuadernos Europeos de Deusto, 2021)
Sustainability studies have not been able to come up with a consensus conceptualization of “sustainability,” despite many attempts. This article asks what this conceptual confusion means. I do this through a (conceptual history) vertical analysis, and horizontal (discourse) analysis of the current use of the term. It finds that sustainability is a perfect fit for what Hupe and Pollit have called a “magic concept,” in that it is; broad, has a positive normative charge, imply consensus or at least the possibility of overcoming current conflicts, and has global marketability (2011: 643). This has both positive and negative effects: On the one hand, the popularity of the concept of sustainability has enabled an overarching discourse on the responsible use of natural resources. On the other hand, the concept is vulnerable to various strategic misuses, ranging from corporate greenwashing to Luddite passions. Based on a vertical analysis of the history of sustainability, this vagueness is not a coincidence: It was part of a political bargain at its birth, where environmental concerns were grafted onto an older discourse on “development” during the writing of the 1987 Brundtland report. Based on a horizontal analysis, this vagueness is now inherent to the concept and cannot be abandoned without losing the very magic qualities that make sustainability such a rallying point. This finding points to the conclusion that we should be cautious about how sustainability is wielded.